Biochemical and radiological markers as predictors of dengue severity in children admitted in a tertiary care hospital - Ravishankar, Kulothungan; N. Vinoth, Ponnurangam; Venkatramanan, Padmasani (International Journal of Contemporary Pediatrics, 2017)
Background: Dengue fever is the arboviral infection with the largest incidence worldwide. Clinical expression of dengue virus infection varies from no symptoms to severe dengue with shock. Severe Dengue is characterized by thrombocytopenia, spontaneous haemorrhages, and gradual plasma leakage that can lead to shock. Biochemical and radiological markers have not been evaluated prospectively in early stages of dengue and their utility as predictors of dengue children progressing to severe dengue have not been studied previously in our part of the country. The objective of this study was to evaluate biochemical and radiological markers as predictors of dengue severity. Methods: This Prospective Cohort study was done in a Tertiary care teaching hospital (Sri Ramachandra Medical College) from January 2010 to June 2011. Children from the age of one month to ≤18 years, who fulfilled the WHO criteria for dengue fever, duration of clinical symptoms < 96 hrs and children with dengue NS 1 antigen positivity with or without IgM antibodies were included in the study. An informed consent was obtained and blood samples were taken for biochemical markers (AST, ALT, CPK and LDH) and radiological markers in the form of plasma leakage was detected by Chest X ray and Ultrasonogram of abdomen. Results: 103 children with dengue infection were enrolled in the study, of which 50 children had warning signs at the time of admission. Among the 50 children with warning signs, 37 children progressed to severe dengue. Serum AST, ALT, CPK and LDH showed significant elevation in children with dengue with warning signs in comparison to children with dengue fever. Radiological markers Chest X-ray and Ultrasonogram abdomen also predicted plasma leakage significantly in children with warning signs than in children with dengue fever. Conclusions: This study suggests that elevated AST, ALT, CPK, LDH, and signs of plasma leak detected within 96 hrs of onset of symptoms can predict a more severe form of dengue infection. Hence, these biochemical and radiological markers may be useful in identification and close monitoring of potentially sick children with dengue infection and serve as valuable prognostic markers early in the course of the illness.